2016
DOI: 10.3847/0004-637x/826/2/130
|View full text |Cite
|
Sign up to set email alerts
|

LARGE-SCALE STRUCTURE AROUND A z = 2.1 CLUSTER

Abstract: The most prodigious starburst galaxies are absent in massive galaxy clusters today, but their connection with largescale environments is less clear at  z 2. We present a search of large-scale structure around a galaxy cluster core at z = 2.095 using a set of spectroscopically confirmed galaxies. We find that both color-selected star-forming galaxies (SFGs) and dusty star-forming galaxies (DSFGs) show significant overdensities around the z = 2.095 cluster. A total of eight DSFGs (including three X-ray luminous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 119 publications
(133 reference statements)
3
14
0
Order By: Relevance
“…Steinhauser et al 2016). In line with these findings, Casey et al (2015) and Hung et al (2016) found slightly higher fractions of irregular and interacting galaxies in the z = 2.47 and 2.10 structures than in their control samples (although with a low statistical significance of ∼ 1.5σ), supporting the influence of galaxy mergers in the evolution of galaxies in overdense environments.…”
Section: Environmental Quenchingsupporting
confidence: 63%
See 2 more Smart Citations
“…Steinhauser et al 2016). In line with these findings, Casey et al (2015) and Hung et al (2016) found slightly higher fractions of irregular and interacting galaxies in the z = 2.47 and 2.10 structures than in their control samples (although with a low statistical significance of ∼ 1.5σ), supporting the influence of galaxy mergers in the evolution of galaxies in overdense environments.…”
Section: Environmental Quenchingsupporting
confidence: 63%
“…Previous studies probing the gas content of galaxies in high density environments suffer from small samples of extreme sources like DSFGs or AGN. In contrast, our study benefits from a relatively large sample of massive galaxies which are spectroscopically-confirmed to be proto-cluster members (drawn from Casey et al 2015;Casey 2016;and Hung et al 2016). As described in detail in the aforementioned references, the targets were selected from several redshift surveys, which followed up cluster candidates from large near-infrared (NIR)-selected catalogs (mostly K-band selected galaxies) in the COSMOS field (e.g.…”
Section: Target Selection and Control Samplementioning
confidence: 99%
See 1 more Smart Citation
“…We also apply our MCMC χ 2 -minimisation method to SCUBA-2 maps of a known DSFG-rich protocluster at z ∼2, PCL1002 (Casey et al 2015;Hung et al 2016), and 256 sources distributed in the COSMOS field in the S2CLS survey. The original COSMOS map is cropped to the central 1 deg × 1 deg region in order to exclude the lower sensitivity edges.…”
Section: Sed Fitting and Photometric Redshiftsmentioning
confidence: 99%
“…Furthermore, there are other z = 3.09 ALMA SMGs outside the AzTEC beam across the entire field of ADF22 ( Figure 7, Table 2). This suggests that intense dusty star formation may also be enhanced by the environment on a large-scale (Umehata et al 2015; see also Blain et al 2004;Tamura et al 2009;Umehata et al 2014;Casey et al 2015;Casey 2016;Hung et al 2016). …”
Section: The Origin Of Multiplicity In a Overdense Environmentmentioning
confidence: 99%